PERANAN ANGGOTA DPRD SUMATERA UTARA FRAKSI PERSATUAN KEADILAN BANGSA DALAM MENGUPAYAKAN ASPIRASI MASYARAKAT - Jannus T.H, Siahaan; Sunaryo Manurung (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UDA, 2020)
The focus of this research is about the Role of Members of the North Sumatra Regional House of Representatives in Fighting for the Aspirations of the People in Accordance with Law Number 32 of 2004 which is replaced by Law Number 23 of 2014 concerning Regional Government, the Regional Representative Council of North Sumatra in particular United Nations Justice Faction. The study was conducted using qualitative descriptive methods. The informants of this study were information from North Sumatra DPRD members from the PKB fraction, PKB fraction staff and administrators. The results showed that the forms of aspirations in the community, namely aspirations in the form of oral, personal, demonstration and work visits. These aspirations are not immediately resolved or given a response but are still through the mechanism of following procedures at the North Sumatra Regional Legislative Institution. The aspirations of the community that have been accommodated will be refined to become a policy, the realization of a policy depends on the executive, on the other hand the legislative body only recommends and oversees all the performance and policies of the executive body.